Integrating evidence from research into decision-making for controlling endemic tropical diseases in South East Nigeria: perceptions of producers and users of evidence on barriers and solutions - Uchenna Ezenwaka; Chinyere Mbachu; Enyi Etiaba; Benjamin Uzochukwu; Obinna Onwujekwe (BMC, 2020)
Abstract Background Endemic tropical diseases (ETDs) constitute a significant health burden in resource-poor countries. Weak integration of research evidence into policy and practice poses a major challenge to the control of ETDs. This study was undertaken to explore barriers to the use of research evidence in decision-making for controlling ETDs. It also highlights potential strategies for addressing these barriers, including the gaps in research generation and utilisation in the context of endemic disease control. Methods Information on barriers and solutions to integrating research evidence into decision-making for controlling ETDs in Anambra State, Nigeria, was collected from 68 participants (producers and users of evidence) during structured discussions in a workshop. Participants were purposively selected and allocated to groups based on their current involvement in endemic disease control and expertise. Discussions were facilitated with a topic guide and detailed notes were taken by an appointed recorder. Outputs from the discussions were synthesised and analysed manually. Results Cross-cutting barriers include a weak research linkage between producers and users of evidence and weak capacity to undertake health policy and systems research (HPSR). Producers of evidence were purported to conceptualise and frame their research questions based on their academic interests and funders' focus without recourse to the decision-makers. Conversely, poor demand for research evidence was reported among users of evidence. Another user barrier identified was moribund research units of the Department of Planning Research and Statistics within the State Ministry of Health. Potential solutions for addressing these barriers include creation of knowledge networks and partnerships between producers and users of evidence, institutionalisation of sustainable capacity-building of both parties in HPSR and revival of State research units. Conclusions Evidence-informed decision-making for controlling ETDs is limited by constraints in the interactions of some factors between the users (supply side) and producers (demand side) of evidence. These constraints could be solved through stronger research collaborations, institutionalisation of HPSR, and frameworks for getting research into policy and practice.